Measurements of propagation velocity of ultrasonic wave at a frequency of 10 MHz in pure and deuterated KDP single crystals - DELEKTA, Olga; OPILSKI, Aleksander (Archives of Acoustics, 1980)
The results of determination of all elastic constants of a KH_2PO_4 single crystal (KDP), and in the case of KD_2xH_2(1-x)PO_4 crystals (DKDP) of constants C_66 i C_11 and the temperature dependence of the constant C66 at a frequency of 10 MHz are reported. The measurements showed an effect of deuteration on the constant C_11 and on the change of the temperature dependence of C_66 in the phase transition region.